PERANAN ORANG TUA DALAM MENGINTERNALISASI PENDIDIKAN AKHLAK KEPADA ANAK - Silahuddin Silahuddin (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2017)
In this era of globalization, Islamic education especially with regard to internalization of moral education face a number of problems. Many factors cause this problem, among others is the lack of the role of parents in shaping the morals of children from an early age. This paper will present about the urgency of the establishment of the morals of children from an early age. This study found that a child will be able to display a noble morals while the good educators, parents, able to understand child psychology began to teach and familiarize children with noble morals since childhood so that the role of the family in the menanankan moral values to children is a very important thing.